Magma Evolution of the Mineral Lake Intrusive Complex, Mellen WI - Guy, John R.; Olson, Christopher J. (My University, 2010)
The Mineral Lake Intrusive Complex (MLIC) of northern Wisconsin is a well-exposed and well-preserved fossil magmatic system of the Mid-Continent Rift at 1.1 Ga. The MLIC is composed of a bimodal suite of compositions that include gabbro and granite. Surprisingly, the intrusive complex has largely escaped careful geochemical analysis. We present new field, geochemical, and petrographic analyses of the MLIC that further constrain its magmatic evolution.
Color poster with text, images, and graphs.
Keywords: Mineral Lake Intrusive Complex (Wis.); Magmas--Wisconsin; Intrusions (Geology)--Wisconsin; Geochemistry--Wisconsin; Posters